A High Gain & Wide Band Rectangular Microstrip Patch Antenna loaded with “Interconnected SRR” Metamaterial Structure - Singhal, Pramod; Garg, Bimal (International Journal of Engineering and Technology, 2012)
Communication applications require wide band and highly directive planner antennas. For such requirement this work deals with the analysis and simulation of a rectangular microstrip patch antenna loaded with “INTERCONNECTED SRR” metamaterial structure at a height of 3.2mm from the ground plane. The work also investigates the potential properties of the proposed metamaterial structure. The proposed Antenna is designed at a operating frequency of 2.75GHz to meet S-Band (2-4GHz) applications. By loading “Interconnected SRR” metamaterial structure with the rectangular patch antenna at a height of 3.2mm, the antenna’s bandwidth is found to be increased up to 378MHz and return loss is reduced to   -42.2dB i.e. the potential properties like return loss, bandwidth, directivity and total efficiency of the proposed antenna increases to a great extent in comparison to the rectangular patch antenna alone.  Double Negative properties of metamaterial have been proved by Nicolson-Ross-weir (NRW) method.